Pengaruh Model Inquiry Based Learning Terintegrasi STEM Terhadap Keterampilan Proses Sains Siswa SMP - Wihdatu Insanil Hakim; Pramudya Dwi Aristya Putra; Sri Rejeki Dwi Astuti (Universitas Muhammadiyah Mataram, 2026)
Abstract: Low science process skills among students remain a problem in science education at the junior high school level. This study aims to determine the effect of the integrated STEM Inquiry Based Learning model on students' science process skills. This study uses a quantitative approach with a quasi-experimental design. The research subjects consisted of two classes, namely the experimental class and the control class, each with 27 students. The research instrument was a science process skills test, while data analysis was performed using normality tests, homogeneity tests, t-tests, and N-Gain tests. The results showed that there was a significant difference in science process skills between the experimental class and the control class. The average N-Gain score for the experimental class was 0.65, which is in the moderate category. These results indicate that the application of the integrated STEM Inquiry Based Learning model is effective in improving the science process skills of junior high school students.Abstrak: Rendahnya keterampilan proses sains siswa masih menjadi permasalahan dalam pembelajaran IPA di tingkat SMP. Penelitian ini bertujuan untuk mengetahui pengaruh model Inquiry Based Learning terintegrasi STEM terhadap keterampilan proses sains siswa. Penelitian ini menggunakan pendekatan kuantitatif dengan desain quasi experiment. Subjek penelitian terdiri atas dua kelas, yaitu kelas eksperimen dan kelas kontrol, masing-masing berjumlah 27 siswa. Instrumen penelitian berupa tes keterampilan proses sains, sedangkan analisis data dilakukan menggunakan uji normalitas, uji homogenitas, uji t, dan uji N-Gain. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan keterampilan proses sains antara kelas eksperimen dan kelas kontrol. Nilai rata-rata N-Gain kelas eksperimen sebesar 0,65 yang termasuk dalam kategori sedang. Hasil ini menunjukkan bahwa penerapan model Inquiry Based Learning terintegrasi STEM efektif dalam meningkatkan keterampilan proses sains siswa SMP.